Changes in Everyday Internet Use and Home Activity During and After Pandemic‐Related Lockdowns: A Case Study in Shuangjing Subdistrict, Beijing. (16th January 2023) - Li, Chunjiang; Thulin, Eva; Chai, Yanwei
Abstract: The outbreak of the COVID‐19 pandemic affected the everyday lives of people. Recent studies have found that Internet use increased during lockdowns and helped people cope with spatial constraints on daily activity. However, long‐term implications on the digitalization of everyday life are still unknown. This study aims to improve the understanding of changes in Internet use during and after lockdown and how these changes relate to home activity and activity context. We draw on a case study of pre‐, mid‐ and post‐lockdown periods in Shuangjing Subdistrict, Beijing. We find that Internet use increased during and after the lockdown, indicating a persistent effect. Home activity mediated the increase in Internet use, suggesting that people stayed at home engaging in more Internet use when restrictions were eased. Work activity and family affairs strengthened the positive impact on Internet use during the lockdown. The influence on Internet use differed depending on sociodemographic characteristics. Abstract : Increase of digitalization of daily activities helps people to cope with COVID‐19 pandemic‐induced spatial constraints on activity and mobility, but what happen after lockdown remain uncertain. This study investigates the changes in internet use in mid‐ and post‐lockdown period and finds: (1) internet use remained elevated post lockdown; (2) home activity mediated positive effect on Internet use in both the mid‐ and post‐lockdown periods; (3) activity type moderated the influence of the lockdown on Internet use.